Osteomielitis esternoclavicular, tratamiento local y sistémico. Reporte de caso. - Alfredo Gutiérrez-Govea (Asociación Colombiana de Infectología, 2021)
Case report of an infrequent disease, approximately 1% of septic arthritis are sternoclavicular, with little response to intravenous antibiotic therapy, requiring ag-gressive surgical management, the following case narrates the excellent response with the use of calcium sulfate pearls impregnated with antibiotics, existing in the literature only cases reports on its use.